“Volumes!”: Den litterære serie på tværs af medier - Tanderup Linkis, Sara (Passage - Tidsskrift for litteratur og kritik, 2018)
Departing from an analysis of Mark Z. Danielewski’s serial novel The Familiar, the article investigates how contemporary literature at once imitates and resists the serial logics of modern media culture. Thus, focusing especially on the aspects of transmediality and participatory culture, I point out how Danielewski’s work adapts the narrative structure as well as the modes of promotion and reception that characterize e.g. modern television series while also positioning itself in contrast to new media culture and emphasizing the ‘literariness’ of the literary series.